Digital Literacy of Accounting Teachers in The Era of Industry 4.0 - Wardoyo, Cipto; Satrio, Yogi Dwi; Rahayu, Dewi (Universitas Negeri Semarang, 2021)
This study aims to address the digital literacy competence of accounting teachers as the subjects in this study. The approach used is qualitative with the type of case study research. Data were collected from interviews and documentation using sources triangulation and techniques triangulation to test the validity of the data. The results showed that the digital literacy competence of accounting teachers in public schools was quite good compared to accounting teachers in private schools. This is supported by adequate IT facilities and regular training. Inhibiting factors experienced by accounting teachers in public schools can be minimized compared to accounting teachers in private schools.